A Pilot Study of Reducing Test Anxiety in a Cohort of Underrepresented in Medicine MCAT Students Using Near-Peer Coaching - Benjamin Liu; Allen Hodge; Crystal Jushka; William J Hueston (University Library System, University of Pittsburgh, 2022)
Background: The Medical College Admission Test (MCAT) is a standardized exam taken by prospective medical students. The MCAT is critical for success in most of the US and parts of Canada, and such pressures may enhance test anxiety. Students from Underrepresented in Medicine (URM) backgrounds are often compounded by being the first in their families to take the MCAT. Methods: We conducted a literature review for interventions on test-related anxiety. Based on our findings, we elected to establish a pilot near-peer coaching (NPC) program for URM students enrolled on the Medical College of Wisconsin MCAT program. We quantified baseline and specific time point test-anxieties using the validated Westside test anxiety scale. We asked about MCAT concerns and program impressions via a free-response section and analyzed the results with inductive analysis. Results: Our review could find no other studies examining MCAT-related test anxiety in the prospective medical student population. NPC was chosen because of its accessibility. At baseline, approximately 50% of students had at least moderately high-test anxiety, meeting the threshold for intervention. Most students perceived themselves as unconfident in their ability to do well on the MCAT. We observed a decrease in test anxiety after coaching sessions. Students received the program well; however, they wanted to be able to choose the content and number of meetings. Conclusion: This observational pilot study suggests that URM pre-medical students have MCAT-related test anxieties high enough to warrant intervention and that NPC is well-received and correlates to reduce test anxiety levels.